Qiliqiangxin improves cardiac function and attenuates cardiac remodelling in doxorubicin-induced heart failure rats - Xutao Sun; Guozhen Chen; Ying Xie; Deyou Jiang; Jieru Han; Fei Chen; Yunjia Song (Taylor & Francis Group, 2020)
Context Therapeutic doxorubicin administration is restricted as this anticancer drug may be cardiotoxic. The traditional Chinese medicine qiliqiangxin has been approved for clinical treatment of chronic heart failure. Objective To explore the protective effects and molecular mechanisms of qiliqiangxin on doxorubicin-induced congestive heart failure (CHF) in rats. Materials and methods A CHF rat model was established via intraperitoneal DOX injections (2.5 mg/kg/week) for 6 weeks. The rats were randomly assigned to control, CHF, CHF + QL (1.0 g/kg/d), or captopril (3.8 mg/kg/d) treatment groups (n = 10) for 4 weeks. MicroRNA sequencing elucidated the molecular mechanisms of qiliqiangxin on doxorubicin-induced CHF in rats. Results Unlike in the CHF group, QL significantly reduced Bax:Bcl-2 (2.05 ± 0.23 vs. 0.94 ± 0.09, p < 0.05) and the levels of collagen I (0.19 ± 0.02 vs. 0.15 ± 0.01, p < 0.05), collagen III (0.19 ± 0.02 vs. 0.14 ± 0.02, p < 0.05), TGF-β1 (5.28 ± 0.89 vs. 2.47 ± 0.51, p < 0.05), Smad3 (1.23 ± 0.12 vs. 0.78 ± 0.09, p < 0.05), MMP-2 (0.89 ± 0.01 vs. 0.53 ± 0.05, p < 0.05), and TIMP-2 (0.24 ± 0.03 vs. 0.44 ± 0.03, p < 0.05). QL also upregulated TGF-β3 (0.65 ± 0.06 vs. 0.96 ± 0.10, p < 0.05) and Smad7 (0.09 ± 0.01 vs. 0.19 ± 0.023, p < 0.05). Moreover, Smad3 was a target of miR-345-3p. Discussion and Conclusions The beneficial effects of QL on DOX-induced CHF in rats are mediated by reduction in myocardial fibrosis, promotion of TGF-β3/Smad7, and inhibition of TGF-β1/Smad3. QL may also modulate specific miRNAs. These results provide evidence that QL might be an effective treatment for DOX-induced CHF.